Pengaruh Profesionalisme dan PengalamanAuditor terhadap Kemampuan Auditor dalam Mendeteksi Kecurangan - Neng Ira; Nofryanti - (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2016)
This study aimed to examine the effect of a professional auditor and the auditor's experience in the auditor's ability to detect fraud. This research was conducted through questionnaires by external auditors who work in the area of Tangerang and South Jakarta. Independent variables used is the professionalism of the auditor and the auditor's experience. The method used in this research is multiple linear regression, correlation test, determination coefficient test, F test, test t. From the results of this study showed that professionalism positive and significant impact on the ability of auditors to detect fraud in this case means that H1 is accepted, as well as the results showed that the auditor's experience has positive and significant impact on the ability of auditors to detect fraud in this case means that H2 is accepted. F Based on the test results indicate that the professionalism and experience of auditor has positive and significant impact on the ability of auditors to detect fraud together it means the H3 is accepted.